The Baby-sitters club. 10, Kristy and the snobs - Chau, Chan.; Martin, Ann M., 1955- (New York, NY : Graphix, an imprint of Scholastic, 2021)
Kristy's family moves to a new neighborhood where the kids make fun of Louie, Kristy's pet collie, who's going blind. The Baby-sitters are not going to let them get away with it.
v. number from spine.
Based on: Kristy and the snobs / Ann M. Martin.
"Based on the novel by Ann M. Martin"--Front cover.
3.2
3-6
3-6
Keywords: Babysitters Club (Imaginary organization) -- Comic books, strips, etc. -- Juvenile fiction; Babysitters -- Comic books, strips, etc. -- Juvenile fiction; Friendship -- Comic books, strips, etc. -- Juvenile fiction; Clubs -- Comic books, strips, etc. -- Juvenile fiction; Babysitters Club (Imaginary organization) -- Fiction; Babysitters -- Fiction; Friendship -- Fiction; Clubs -- Fiction; Cartoons and comics; Babysitters Club (Imaginary organization) -- Comic books, strips, etc. -- Fiction; Babysitters -- Comic books, strips, etc. -- Fiction; Friendship -- Comic books, strips, etc. -- Fiction; Clubs -- Comic books, strips, etc. -- Fiction